Curriculum Management To Optimize Islamic Studies Course At The Public Universities - Mukniah Mukniah (TADRIS: Jurnal Pendidikan Islam, 2018)
Public universities (hence abbreviated: PTU) and Religious universities (abbreviated: PTA) are different from each other. PTA focus on studies of specific religion, while PTU deal with general knowledge not even related to religious dogma. Nevertheless, Indonesian education system needs to take account of curriculum management—as the proces of planning, organizing, implementing and evaluating curriculum—especially for the subject of Islamic studies (abbreviated: PAI, stands for Pendidikan Agama Islam) at the public universities (PTU). However, the subject of Curriculum Management and Islamic studies (PAI) are frequently considered to be additional subjects, yet in fact they could play a pivotal role as subjects for character building (MPK). Therefore, these particular subjects should be taken into account by the decision makers. The reserach was aimed at analysing and identifying the appropriate model of curriculum management and education to optimise Islamic studies (PAI) course at the public unversities (PTU).Keywords: Management, Curriculum, Islamic Education, Public Universities